Effect of vermicompost and chitin on the control of Meloidogyne incognita in greenhouse tomato - Castro, Leida (2010)
Meloidogyne incognita is a sedentary endoparasitic nematode, with total penetration and gall-forming; it has a wide geographical distribution and causes significant agricultural losses. Recently, organic fertilizers and compounds such as chitin have been used in the suppression of plant pests and diseases. The aim of this study was to evaluate the effect of applying cattle manure vermicompost, and its enrichment with chitin, on the infection of M. incognita in tomato plants var. Hayslip under greenhouse conditions. For this purpose, plants were inoculated with 5000 units of eggs+second stage juveniles per pot and were compared with controls grown in soil without organic amendment or chitin. The evaluation was carried out 60 days afterwards: the shoot and root fresh weight, shoot dry weight, total population in root and soil nematodes, root knot index (INR), rate of egg masses (IMH), the nematode reproduction factor (FR) and functional-groups numbers (fungi, bacteria and actinomycetes) were measured. The addition of vermicompost to soil caused an increase in the variables of shoot fresh and dry weight and fresh root weight:the higher the percentage of vermicompost, the higher the increase; likewise, the application of vermicompost reduced the number of nematodes both in root and soil. The application of chitin accentuated these results by bringing about the lowest reproduction factor of M. incognita, with a value of 3.76 for the dose of vermicompost+50% chitin, whereas in the control this factor had a value of 93.20. The application of chitin as sole amendment affected only the soil fungi population, while the actinomycetes population increased in the amended treatments.